Mesenchymal Stem Cell Therapy for Cardiac Inflammation: Immunomodulatory Properties and the Influence of Toll-Like Receptors - F. van den Akker; S. C. A. de Jager; J. P. G. Sluijter (Mediators of Inflammation, 2013)
Background. After myocardial infarction (MI), the inflammatory response is indispensable for initiating reparatory processes. However, the intensity and duration of the inflammation cause additional damage to the already injured myocardium. Treatment with mesenchymal stem cells (MSC) upon MI positively affects cardiac function. This happens likely via a paracrine mechanism. As MSC are potent modulators of the immune system, this could influence this postinfarct immune response. Since MSC express toll-like receptors (TLR), danger signal (DAMP) produced after MI could influence their immunomodulatory properties. Scope of Review. Not much is known about the direct immunomodulatory efficiency of MSC when injected in a strong inflammatory environment. This review focuses first on the interactions between MSC and the immune system. Subsequently, an overview is provided of the effects of DAMP-associated TLR activation on MSC and their immunomodulative properties after myocardial infarction. Major Conclusions. MSC can strongly influence most cell types of the immune system. TLR signaling can increase and decrease this immunomodulatory potential, depending on the available ligands. Although reports are inconsistent, TLR3 activation may boost immunomodulation by MSC, while TLR4 activation suppresses it. General Significance. Elucidating the effects of TLR activation on MSC could identify new preconditioning strategies which might improve their immunomodulative properties.